Association of Gestational Age at Birth With Subsequent Neurodevelopment in Early Childhood: A National Retrospective Cohort Study in China - Jing Hua; Anna L. Barnett; Yao Lin; Hongyan Guan; Yuanjie Sun; Gareth J. Williams; Yuxuan Fu; Yingchun Zhou; Wenchong Du (Frontiers Media S.A., 2022)
BackgroundThe association between preterm birth and neurodevelopmental delays have been well examined, however, reliable estimates for the full range of gestational age (GA) are limited, and few studies explored the impact of post-term birth on child development.ObjectiveThis study aimed to examine the long-term neuropsychological outcomes of children born in a full range of GA with a national representative sample in China.MethodsIn this retrospective population-based cohort study, a total of 137,530 preschoolers aged 3-5 years old (65,295/47.5% females and 72,235/52.5% males) were included in the final analysis. The Ages and Stages Questionnaires-Third Edition (ASQ-3) was completed by parents to evaluate children's neurodevelopment. The associations between GA and neurodevelopment were analyzed by a generalized additive mixed model with thin plate regression splines. Logistic regression was also conducted to examine the differences in children's development with different GAs.ResultsThere was a non-linear relationship between GA and children's neurodevelopmental outcomes with the highest scores at 40 weeks gestational age. The adjusted risks of GAs (very and moderately preterm, late-preterm, early-term, and post-term groups) on suspected developmental delays were observed in communication (OR were 1.83, 1.28, 1.13, and 1.21 respectively, each p < 0.05), gross motor skill (OR were 1.67, 1.38, 1.10, and 1.05 respectively, each p < 0.05), and personal social behavior (OR were 1.01, 1.36, 1.12, and 1.18 respectively, each p < 0.05). The adjusted OR of very and moderately preterm, late-preterm, and early-term were observed in fine motor skills (OR were 1.53, 1.22, and 1.09 respectively, each p < 0.05) and problem-solving (OR were 1.33, 1.12, and 1.06 respectively, each p < 0.05).ConclusionGAs is a risk factor for neurodevelopmental delays in preschoolers after controlling for a wide range of covariates, and 40-41 weeks may be the ideal delivery GA for optimal neurodevelopmental outcomes. Close observation and monitoring should be considered for early- and post-term born children as well as pre-term children.